TESTER TOLERANCE SOME OF LOCAL MAIZE TO THE SALINITY STRESS ON PHASE OF GERMINATION - SARJUN HENDRY SIGALINGGING; DWI ZULFITA; ASNAWATI ASNAWATI (Jurnal Sains Pertanian Equator, 2018)
ABSTRACT                                                                                                                    One of the obstacles in increasing the production of maize is salinity stress. Not all varieties that have been developed have good tolerance to stressful environments especially on saline areas. Therefore, the purpose of this research was to obtain local varieties of maize tolerant to salinity stress in the germination phase. The initial step to obtain salinity tolerant maize varieties was to test the tolerance of several local varieties to be assessed for their tolerance level based on the used NaCl concentration of 0,8%. The design used in this research is Completely Random Design (RAL) consisting of 8 varieties with 4 replications. Each treatment consists of 2 sets. The first set is used to measure the vigor index, and the germinating power. The second set is used to measure the growth rate, plumula length, root length, and normal dry weight of sprouts. Varieties used in this research are varieties Lamuru, Sukmaraga, Srikandi Kuning, Srikandi Putih, Bantil, Ensalang, Jagung Susu, and Semoncol. The result of the research showed that there was no local corn varieties tolerant to salinity stress in germination phase with mean value of Giving Power below 50%.  Keywords: Drought Stress, NaCl Sodium Chloride, Local Maize.